Successful Treatment of de Quervain Tenosynovitis With Ultrasound‐guided Percutaneous Needle Tenotomy and Platelet‐Rich Plasma Injection: A Case Presentation. Issue 5 (21st May 2013) - Peck, Evan; Ely, Erin
Abstract : De Quervain tenosynovitis is a disorder of the tendons of the first dorsal compartment of the wrist that causes pain and functional disability, which may be refractory to conservative treatments. We present a case of ultrasound‐guided percutaneous needle tenotomy and platelet‐rich plasma injection for the successful treatment of de Quervain tenosynovitis.